No shadows in the desert : murder, vengeance, and espionage in the war against ISIS - Katz, Samuel M., 1963- (Hanover Square Press, 2020)
"The inside story of the covert operation that took down the heads of ISIS. No Shadows in the Desert reveals the untold story of the behind-the-scenes fight against ISIS--one coordinated by heads of state and ultimately fought in the alleyways and open deserts of the Middle Eastern battlefield by spies and soldiers. Samuel M. Katz draws upon his sources within the global intelligence and counterterrorism community, as well as the international special operations and espionage fraternity, to tell the story of the covert campaign against ISIS by the operatives who ventured deeply and secretly into enemy territory. In this first-ever look at the secret inner workings of an Arab secret service, Katz tells the story of Jordan's GID, the masters of human intelligence on the espionage battlefields of the Middle East, who proved pivotal and crucial go-to allies of the CIA and America's other intelligence agencies in the war against ISIS and the war on terror. With the revealing and intimate insight of the intelligence officers who fought ISIS, No Shadows in the Desert is a rare glimpse into how a strategic partnership helped change how terrorism is fought in the Middle East and beyond."--Jacket flap.